Remotely distinguishing and mapping endogenic water on the Moon. (28th May 2017) - Klima, Rachel L.; Petro, Noah E.
Abstract : Water and/or hydroxyl detected remotely on the lunar surface originates from several sources: (i) comets and other exogenous debris; (ii) solar-wind implantation; (iii) the lunar interior. While each of these sources is interesting in its own right, distinguishing among them is critical for testing hypotheses for the origin and evolution of the Moon and our Solar System. Existing spacecraft observations are not of high enough spectral resolution to uniquely characterize the bonding energies of the hydroxyl molecules that have been detected. Nevertheless, the spatial distribution and associations of H, OH − or H2 O with specific lunar lithologies provide some insight into the origin of lunar hydrous materials. The global distribution of OH − /H2 O as detected using infrared spectroscopic measurements from orbit is here examined, with particular focus on regional geological features that exhibit OH − /H2 O absorption band strengths that differ from their immediate surroundings. This article is part of the themed issue 'The origin, history and role of water in the evolution of the inner Solar System'.